Maternal Depression and Early Parenting: A Comparison Between Culturally and Linguistically Diverse and Australian born Mothers. (February 2022) - Eatt, Jodi; Watson, Stuart J; Ball, Helen L.; Sevar, Katherine; Galbally, Megan
Objective: To examine the risk of perinatal depression, parenting stress and infant sleep practices in Australian culturally and linguistically diverse (CaLD) women. Method: Within the Mercy Pregnancy and Emotional Wellbeing Study, we examined 487 pregnant women of whom 52 were CaLD and 435 non-CaLD. Depression was measured using the Structured Clinical Interview for DSM-IV and the Edinburgh Postnatal Depression Scale. In addition, Parenting Stress Index and infant sleep measures were collected. Results: Fewer CaLD women had a depression diagnosis but there were no differences between CaLD and non-CaLD women for perinatal mental health symptoms. More mothers in the CaLD group were bed sharing with their infant during the night at six months; however, bedsharing was only associated with higher parenting stress for non-CaLD mothers. Conclusions: Findings suggest both differences in infant sleep parenting practices and in parenting stress but not general emotional wellbeing. Future research is required to replicate these findings.